(untitled) (Acta Polytechnica CTU Proceedings, 2020)
Nuclear-related sciences and technology have a long and rich history within the Czechoslovakia. Even though the Czech Republic and Slovakia have been separated since 1993, wide cooperation on different levels including education and research still exists. In order to support cooperation and good relations between Czech and Slovak students in nuclear engineering and related disciplines, the Department of Nuclear Reactors organizes annually a student conference on nuclear engineering - Šimáně. Students mainly from Czech and Slovakian nuclear institutes are invited to present their research and share their knowledge. Participants from other foreign institutes are welcomed as well. The conference is named after professor Šimáně, who graduated at the Dr. Edvard Beneš Technical University in Brno. He was born in May 1919 which means that he would celebrate his 100th birthday just before this year’s conference. During his early career, he had the opportunity to work with Fréderic Joliot-Curie at College de France. Later, he significantly contributed to the foundation of the nuclear science, industry and education in the Czechoslovakia. He became the first employee of the Institute of Nuclear Physics at the Czechoslovakian Academy of Science, later he became the first director of the Nuclear Research Institute in Řež. Professor Šimáně was well established even on the international level. He was a director at the Joint Institute of Nuclear Research in Dubna or a division director at the International Agency for Atomic Energy. His work was also significantly connected with Faculty of Nuclear Sciences, CTU in Prague where he acted as Dean from 1967 to 1972. The main objective of the conference is to provide an opportunity for BSc., MSc. and Ph.D. students of nuclear-oriented study programmes to publish and present their scientific results achieved during their university studies. Furthermore, it should give the participants experience in the field of presenting their own research, writing scientific papers and also broaden their knowledge throughout the related fields and to remind them rich Czechoslovakian history in nuclear fields by inviting experienced experts. The organizing committee would like to thank all participants for their contributions and also to the CTU in Prague for funding this student conference. The committee also hopes that the work achieved and presented will fulfill the heritage of professor Čestmír Šimáně in current as well as future conferences. Date: June 1 - 2, 2020 Venue: Prague, Czech Republic URL: http://simane.fjfi.cvut.cz Organized by: Department of Nuclear Reactors, Faculty of Nuclear Sciences and Physical Engineering, Czech Technical University in Prague Guest editor: Martin Ševeček Scientific committee: Martin Cesnek Ondřej Novák Pavel Suk Local organizing committee: Adam Kecek Vojtěch Caha Guarantor of the peer review process: Milan Štefánik Guarantor of language editing: Martin Cesnek